Pembelajaran Pengembangan Destinasi Wisata Kebugaran di Prov. DIY dan Prov. Bali sebagai Potensi Produk Wisata di Ibu Kota Negara - Cathelya Yosephine Hotasina (JOURNAL OF APPLIED SCIENCE (JAPPS), 2023)
Wellness tourism is a new genre in world tourism, although so far world tourists are familiar with spa treatments or activities in hot springs as part of holiday packages in the travel and tourism industry. In fact, for Indonesia, wellness is a potential tourism resource, especially when associated with various existing elements of tradition and culture. Indonesia's deeply rooted cultural identity has become one of Indonesia's strengths in developing various health and herbal/herb tourism products. The emergence of wellness tourism itself cannot be separated from lifestyle changes to be better and healthier (wellbeing lifestyle), especially in a world that is experiencing a pandemic like this. Nevertheless, wellness tourism products cannot be separated from the main and supporting tourism products, which are the main motives for tourist visits to a destination. Therefore, the collaboration between local wellness tourism resources and various main tourism resources is the main reason why this wellness tourism develops in destinations that have special functions that encourage people from outside the destination to come to visit, one of which is in the National Capital. This study aims to study how Yogyakarta and Bali, as a major tourist destination in Indonesia, is able to develop wellness tourism products that are rooted in their traditions and culture, even as a companion to their main tourist attractions. Using a qualitative descriptive analysis method on the results of interviews, observations and concentrated discussions conducted with all stakeholders, both from the government and tourism industry players, this research then produced several keys to the successful development of wellness tourism products in the two destinations, such as cultural strengths related to wellness, favorable regulations, geographical position and so forth. This strength then becomes a lesson that can be adapted to be developed in the Archipelago, as the future Capital of the Republic of Indonesia